Association of mitochondrial haplogroup H with reduced risk of type 2 Diabetes among Gulf Region Arabs - Dashti, Mohammed; Ali, Naser M.; Alsaleh, Hussain; John, Sumi Elsa; Nizam, Rasheeba; Thanaraj, Thangavel Alphonse; Al-Mulla, Fahd (Frontiers in Endocrinology, 2024)
Background: Numerous studies have linked mitochondrial dysfunction to the development of type 2 diabetes (T2D) by affecting glucose-stimulated insulin secretion in pancreatic beta cells and reducing oxidative phosphorylation in insulin-responsive tissues. Given the strong genetic underpinnings of T2D, research has explored the connection between mitochondrial DNA haplogroups, specific variants, and the risk and comorbidities of T2D. For example, haplogroups F, D, M9, and N9a have been linked to an elevated risk of T2D across various populations. Additionally, specific mitochondrial DNA variants, such as the rare mtDNA 3243 A>G and the more prevalent mtDNA 16189 T>C, have also been implicated in heightened T2D risk. Notably, these associations vary among different populations. Given the high incidence of T2D in the Gulf Cooperation Council countries, this study investigates the correlation between T2D and mitochondrial haplogroups and variants in Arab populations from the Gulf region. Methods: This analysis involved mitochondrial haplogroup and variant testing in a cohort of 1,112 native Kuwaiti and Qatari individuals, comprising 685 T2D patients and 427 controls. Complete mitochondrial genomes were derived from whole exome sequencing data to examine the associations between T2D and haplogroups and mitochondrial DNA variants. Results: The analysis revealed a significant protective effect of haplogroup H against T2D (odds ratio [OR] = 0.65; P = 0.022). This protective association persisted when adjusted for age, sex, body mass index (BMI) and population group, with an OR of 0.607 (P = 0.021). Furthermore, specific mitochondrial variants showed significant associations with T2D risk after adjustment for relevant covariates, and some variants were exclusively found in T2D patients. Conclusion: Our findings confirm that the maternal haplogroup H, previously identified as protective against obesity in Kuwaiti Arabs, also serves as a protective factor against T2D in Arabs from the Gulf region. The study also identifies mitochondrial DNA variants that either increase or decrease the risk of T2D, underscoring their role in cellular energy metabolism.